Smart Money In This Economy: Sosialisasi Literasi Finansial Masyarakat Gen Z Banjarmasin sebagai Fondasi Pertumbuhan Ekonomi Indonesia - Anisa Fadhila Rahmi; Nadya Putri Ahlina; Nasya Amanda Rifianti; Nisrina Najla Deasianti; Syarofah Zahra; Anna Nur Faidah; Sudirwo Sudirwo (Jurnal Pengabdian Masyarakat Waradin, 2026)
Generation Z is recognized as a group that is adaptive to technological developments; however, they still face serious challenges in terms of financial management. Based on the National Survey of Financial Literacy and Inclusion by the Financial Services Authority (OJK) in 2022, the level of financial literacy in South Kalimantan is still far below the national average, at only 42.88% compared to 49.68%. This low level of financial literacy often triggers consumptive behavior and lack of responsibility in financial decision-making. This community service activity aims to enhance comprehensive understanding of financial literacy, build skills in financial management and recording, and foster interest in safe investment through education digitalization. The implementation method includes material delivery through socialization, followed by discussion and question-and-answer sessions, as well as evaluation using Pre-Test and Post-Test instruments. The results of the activity demonstrate an increase in understanding, as reflected by the increase in the average scores from 75,33 in the Pre-Test to 100 in the Post-Test, indicating a 24,67% improvement. Thus, this activity not only enhanced understanding but also fostered awareness of the importance of wise financial management in the face of digital economic challenges.